Endophytic Fungi from Frankincense Tree Improves Host Growth and Produces Extracellular Enzymes and Indole Acetic Acid - Khan, Abdul Latif; Al-Harrasi, Ahmed; Al-Rawahi, Ahmed; Al-Farsi, Zainab; Al-Mamari, Aza; Waqas, Muhammad; Asaf, Sajjad; Elyassi, Ali; Mabood, Fazal; Shin, Jae-Ho; Lee, In-Jung (PloS one, 2016)
Boswellia sacra, an economically important frankincense-producing tree found in the desert woodlands of Oman, is least known for its endophytic fungal diversity and the potential of these fungi to produce extracellular enzymes and auxins. We isolated various fungal endophytes belonging to Eurotiales (11.8%), Chaetomiaceae (17.6%), Incertae sadis (29.5%), Aureobasidiaceae (17.6%), Nectriaceae (5.9%) and Sporomiaceae (17.6%) from the phylloplane (leaf) and caulosphere (stem) of the tree. Endophytes were identified using genomic DNA extraction, PCR amplification and sequencing the internal transcribed spacer regions, whereas a detailed phylogenetic analysis of the same gene fragment was made with homologous sequences. The endophytic colonization rate was significantly higher in the leaf (5.33%) than the stem (0.262%). The Shannon-Weiner diversity index was H' 0.8729, while Simpson index was higher in the leaf (0.583) than in the stem (0.416). Regarding the endophytic fungi's potential for extracellular enzyme production, fluorogenic 4-methylumbelliferone standards and substrates were used to determine the presence of cellulases, phosphatases and glucosidases in the pure culture. Among fungal strains, Penicillum citrinum BSL17 showed significantly higher amounts of glucosidases (62.15±1.8 μM-1min-1mL) and cellulases (62.11±1.6 μM-1min-1mL), whereas Preussia sp. BSL10 showed significantly higher secretion of glucosidases (69.4±0.79 μM-1min-1mL) and phosphatases (3.46±0.31μM-1min-1mL) compared to other strains. Aureobasidium sp. BSS6 and Preussia sp. BSL10 showed significantly higher potential for indole acetic acid production (tryptophan-dependent and independent pathways). Preussia sp. BSL10 was applied to the host B. sacra tree saplings, which exhibited significant improvements in plant growth parameters and accumulation of photosynthetic pigments. The current study concluded that endophytic microbial resources producing extracellular enzymes and auxin could establish a unique niche for ecological adaptation during symbiosis with the host Frankincense tree.